Estudo e preservação do acervo de cerâmica da Faculdade de Belas-Artes da Universidade de Lisboa - Sousa, Mariana de Figueiredo (2019)
The following dissertation presents a project that started from the need of patrimonial safeguarding of the collection of ceramics of the Faculty of Fine Arts of the University of Lisbon. This work intends, from the union of several disciplinary fields, to make the student and teacher’s community aware of the need to implement a preventive conservation plan for this collection, averting its loss. For this purpose, the inventory, analysis and study of this collection, consisting of more than 2 500 ceramic pieces, were carried out, in which several cores, such as the old tiles, from the 17th and 18th centuries, sculptures and panels of contemporary tiles dating from 1974 to the present. Offering immeasurable value, this collection was formed from pieces collected and kept for their pedagogical functions and for their aesthetic and formal value, which make them representative of the techniques, plastic expressions and aesthetic options developed by students and teachers over the years in the discipline of ceramics. In fact, from this study, one can understand the evolution of teaching dedicated to "Ceramic Technology", from the appearance of this discipline to the present, within the scope of the reforms in the teaching of Fine Arts of the 20th century, and its changes in curricula. After the initial study, dedicated to the constitution of this collection, it is presented a risk analysis and a set of preservation and preventive conservation measures to be implemented in the institution, in which inventory, management and organization of the collection are fundamental. For this purpose, a description of the ideal conditions of conservation and conditioning of the storage room is made, proposing sustainable and feasible solutions adapted to the case under study and to the existing resources. In the last part of this project, in addition to the implementation of this proposal, it is also referred to the dissemination, awareness and valorisation of the collection, encouraging future research and musealization projects. In the work presented, it is evident that this collection constitutes an essential part of the teaching of ceramics and the learning of several generations of national artists in the FBAUL, part of the collective memory of the student and teacher’s community, deserving a solid incorporation policy so that can continue to grow as a form of artistic testimony for future generations of students and artists